Comparison Between Glasgow Come Scale (GCS) and Systolic Pressure With Mortality In 12 Hours Of Patient severe Head Injury In The Provincial Hospital dr. Moewardi in surakarta - Anissa Cindy Nurul Afni; Fakhrudin Nasrul Sani (Universitas Sari Mulia, 2018)
Background: Traumatic Coma Data Bank (TCDB) recorded mortality rates from head injury less than 17 for 100,000 victims outside the hospital and 6 for 10,000 victims taken to hospital. The impact of head injuries provide the more complex of disorders such as impaired neurological function, disability, and death. Primary and secondary damage occurred in 6-12 the first hour against the structure and contents of the physiological anatomik skull. The main factor of survival of the patient with head injury was the value of the GCS and the systolic pressure.Purpose: The research of identified correlation between GCS and systolic pressure with mortality in 12 hours of patient severe head injury. Methods : This prospective study was conducted at The Provincial Hospital Dr. Moewardi in Surakarta with medical record study descriptive correlative crossectional approach and retrospective design. Sample taken with the technique of quota sampling with 50 total sample of respondents. The bivariat analysis used in this research is Fisher test.Conclusion : There is a relationship between GCS with mortality in 12 hours of severe head injury patient. There was no relationship between systolic blood pressure with mortality in 12 hours of severe head injury patient. Key Words: head injury, severe head injury, mortality of head injured patient, GCS, systolic pressure.